Superconducting HTS coil made from round cable cooled by liquid nitrogen flow. (15th September 2017) - Šouc, J; Gömöry, F; Vojenčiak, M; Seiler, E; Kováč, J; Frolek, L
Abstract: The concept of simple cooling arrangement for superconducting coil made from a round cable based on high-temperature superconductor tapes is demonstrated. The cable architecture is similar to the Conductor on Round Core (CORC ® ) concept: it consists of eight superconducting tapes wound in two layers on a copper tube core in a helical manner. Such a Conductor on Round Tube hand-made cable 4 m long was used to wind the coil with eight turns on 14 cm diameter. Layers of commercial aerogel and polyurethane foam were applied to the coil to provide vacuum-less thermal insulation at its cooling by the flow of liquid nitrogen (LN) in the cable tube. The temperature of superconducting tapes was around 1 K above the coolant temperature in these conditions, causing about 16% reduction of the critical current compared to the LN bath cooling. Electromagnetic performance of the coil was calculated by the model based on the finite element method and the results compared with experimental observations.